'I Got Your Six—Maybe': A Drafted Versus Volunteer Bond, A Drafted Versus Volunteer Loss. (3rd April 2018) - Ferguson, Lisa
Abstract : I argue that the bonds formed among drafted soldiers during the Vietnam War surpass the bonds of today's 'career soldiers' due to the Vietnam vets' dissimilar backgrounds, the nation's collective scorn for their service, and their lack of training. Today's servicemen and women enjoy common interests, national support, and intense preparation. However, these seemingly positive changes have prevented them from developing the connections needed to help them mentally navigate their tour of duty and their post-war reality. I use two Vietnam War novels, Larry Heinemann's Close Quarters and Tim O'Brien's The Things They Carried, as examples of men who had the most disadvantageous of circumstances yet formed the strongest of bonds. Conversely, I analyse Kevin Powers' Iraq War novel, The Yellow Birds, and discuss how the shaky relationship between Bartle and Murph proves that today's fighting men and women are ultimately disconnected from each other and therefore have no 'love stories' to tell.